Arm-length-dependent phase transformation and dual dynamic healing behavior of supramolecular networks consisting of ureidopyrimidinone-end-functionalized semi-crystalline star polymers. (5th September 2020) - Lee, Woojin; Kwak, Seung-Yeop; Chung, Jae Woo
Graphical abstract: The appropriate arm-length balance of UPy-end-functionalized star-shaped poly(ε-caprolactone)s (USPs) can provide a mechanically rigid semi-crystalline supramolecular network with highly efficient healing property. Abstract: A rigid crystalline structure suppresses chain mobility and diffusion of self-healing supramolecular networks, lowering their healing capabilities. Herein it is presented that the incorporation of crystals in self-healing supramolecular networks as an effective way to overcome the inherent lack of mechanical strength of self-healing supramolecular networks, instead of a healing barrier. We prepare dual dynamic supramolecular networks composed of two types of dynamic physical bonds, i.e., quadruple hydrogen bonds and crystalline physical bonds, using the ureidopyrimidinone (UPy)-end-functionalized semi-crystalline star-shaped poly(ε-caprolactone)s (USPs). With increasing arm-length of the USPs, the phase of the network changes from UPy-stacked crystals to an amorphous phase and further to chain-folding polymeric crystals. The healing capabilities are also enhanced with increasing the arm-length of the USPs. Such changes in phase and healing capability are strongly associated with the crosslinking density of the network. In addition, the appropriate arm-length balance of USPs can provide a mechanically rigid semi-crystalline supramolecular network with a highly efficient healing property due to their reversible dual dynamic features, associated with the re-association of UPy quadruple hydrogen bonds and restoration of crystalline physical bonds during healing.